Penerapan Metode Six Sigma dan Failure Mode Effect Analyze Untuk Meminimalisasi Defect di PT. ABC - Handy Natan Permana; Dwi Sukma Donoriyanto (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
This study aims to determine the number of rejected products (products that do not meet consumer and company standards) for 220 mL cup products using the six sigma method with 5 stages (define, measure, analyze, improve, and control) which will then be given improvement recommendations using failure mode effect analyze (FMEA). After going through the calculation process, it is known that the company's Deffect Per Million Opportunity (DPMO) value is 3.67 which indicates that the percentage of production without deffects is 96.32%. There are four critical to process (CTQ) in the 220 mL cup defect and the largest is the skewed seal with a percentage of 70%. The results of calculations using risk priority number (RPN) found recommendations in the form of corrective actions in 80% of the group of causes of oblique seal deffects so that it is hoped that the company will review and make improvements to the proposal so as to reduce deffects per million opportunity (DPMO) in the 220 mL cup production unit.